Enhancing food engineering education with interactive web-based simulations - Alexandros Koulouris; Georgios Aroutidis; Dimitris Vardalis; Petros Giannoulis; Paraskevi Karakosta (International Journal of Food Studies)
In the traditional deductive approach in teaching any engineering topic, teachers would first expose students to the derivation of the equations that govern the behavior of a physical system and then demonstrate the use of equations through a limited number of textbook examples. This methodology, however, is rarely adequate to unmask the cause-effect and quantitative relationships between the system variables that the equations embody. Web-based simulation, which is the integration of simulation and internet technologies, has the potential to enhance the learning experience by offering an interactive and easily accessible platform for quick and effortless experimentation with physical phenomena. This paper presents the design and development of a web-based platform for teaching basic food engineering phenomena to food technology students. The platform contains a variety of modules (“virtual experiments”) covering the topics of mass and energy balances, fluid mechanics and heat transfer. In this paper, the design and development of three modules for mass balances and heat transfer is presented. Each webpage representing an educational module has the following features: visualization of the studied phenomenon through graphs, charts or videos, computation through a mathematical model and experimentation. The student is allowed to edit key parameters of the phenomenon and observe the effect of these changes on the outputs. Experimentation can be done in a free or guided fashion with a set of prefabricated examples that students can run and self-test their knowledge by answering multiple-choice questions.